Strategy and Impact of Educational Videos on the Dangers of Smoking on Instagram by the Makassar’s Health Department Through Collaboration with Local Influencers - Nur Inayah Ismaniar; Samsiana (Asian Journal of Environmental Research, 2025)
Indonesia faces a persistently high prevalence of smoking, particularly among adolescents, necessitating innovative communication strategies to promote tobacco control. This study aims to analyze the strategy and impact of the Makassar Health Department’s collaboration with local influencers in disseminating anti-smoking educational videos on Instagram. Using a qualitative descriptive approach, data were collected through in-depth interviews with program managers at the Makassar Health Department and observation of seven uploaded videos. Engagement Rate (ER) was calculated based on likes, comments, and shares to assess audience interaction. Results indicate that Instagram serves as an effective medium for health behavior change communication, reaching younger demographics through culturally resonant and emotionally engaging content. The collaboration with local influencers enhanced message relatability and expanded audience reach beyond official government channels. The highest ER was achieved by influencer Uyha Yasashaky with 296%, suggesting exceptionally high engagement and viral diffusion. The findings reveal that this partnership exemplifies the two-step flow of communication model, where trusted public figures act as intermediaries between health authorities and the public. Moreover, institutional leadership and resource support from the Makassar Health Department ensured message consistency and alignment with broader public health objectives. In conclusion, the strategic use of local influencers on social media proved to be a highly effective approach for amplifying tobacco control messages, increasing public engagement, and reinforcing healthy behavioral norms within the sociocultural context of Makassar.